Assessment of The UTCI and HSI Biometeorological Indices for Constanța and Tulcea. - Maria Julia PETRE (Riscuri şi Catastrofe)
The present work aims to make a contribution to raising the level of awareness regarding the influence of environmental factors on the human community, by calculating two biometeorological indices, namely Universal Thermal Climate Index (UTCI) and Heat Stress Index (HSI), which provide quantitative assessments of the thermal stress experienced by human populations in the examined region. Therefore, using the Bioklima software, the two biometeorological indices were calculated based on meteorological parameters recorded at the Constanța and Tulcea meteorological stations during the period from 2016 to 2022. Consequently, the results obtained based on the analysis of the extreme values of the UTCI index, indicate “no thermal stress” as the category of thermal comfort with the highest frequency during the studied years, at both stations. At the same time, the maximum HSI values suggest that the thermal comfort category “slight and moderate heat stress” was the most prevalent during the analyzed period at the Constanța meteorological station, while at Tulcea the most frequent thermal comfort category was “slight cool stress”. It is noteworthy that, although these desirable thermal comfort categories were predominant, categories illustrating weather conditions that pose a threat to the health of organisms (particularly humans) were also recorded during the studied years.